Codoping Effect of Nitrogen (N) to Iron (Fe) Doped Zirconium Titanate (ZrTiO4) Composite toward Its Visible Light Responsiveness as Photocatalysts - Rizka Hayati; Rian Kurniawan; Niko Prasetyo; Sri Sudiono; Akhmad Syoufian (Indonesian Journal of Chemistry, 2022)
Iron (Fe) and nitrogen (N) were introduced as dopants into zirconium titanate (ZrTiO4) in order to study the codoping effects of nitrogen on iron-doped zirconium titanate (Fe,N-codoped ZrTiO4) composite. Titanium tetraisopropoxide (TTIP), zirconia (ZrO2), urea, and iron(II) sulfate heptahydrate were used as the source of TiO2, semiconductor supports, source of nitrogen, and iron, respectively. A specific amount of iron (1, 3, 5, 7, and 9 wt.%) and a fixed nitrogen content (10 wt.%) were doped into the ZrTiO4 lattice. Various calcination temperatures (from 500 to 900 °C) were also applied to investigate the crystal structure of the composite. The composites were characterized by X-ray powder diffractometer (XRD), Fourier-transform infrared spectrophotometer (FT-IR), scanning electron microscope with energy dispersive X-Ray spectrometer (SEM-EDX), and specular reflectance UV-Vis (SR-UV). The lowest bandgap energy of 2.62 eV was obtained in the composite with 3 wt.% of Fe and 10 wt.% of N calcined at 500 °C.